2019
DOI: 10.11647/obp.0189
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure Investment in Indonesia

Abstract: This monograph maps the research journey undertaken by the policy and finance team within the infrastructure cluster of the Australia-Indonesia Research Centre. An outline of the research approach and collaboration is provided in the paper titled 'Collaborative international industry-university research training in infrastructure projects: an Australian-Indonesian case study' by Hui et al. 2018. 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…This quantitative gap not only represents a significant research challenge but also encourages the exploration of alternative perspectives, considering the potential benefits arising from addressing this gap and the inherent consciousness. Meanwhile in Indonesia, some research that shown correlation between regional growth with development of infrastructure just indicated by regression of several factor to provide a correlation with economic growth which has an impact on measurement of infrastructure development in Indonesia but, that's several research doesn't explore the correlation over the other regional growth's parameter [5,6,8,19,20]. This gap in empirical assessment is the focus of our research investigation.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This quantitative gap not only represents a significant research challenge but also encourages the exploration of alternative perspectives, considering the potential benefits arising from addressing this gap and the inherent consciousness. Meanwhile in Indonesia, some research that shown correlation between regional growth with development of infrastructure just indicated by regression of several factor to provide a correlation with economic growth which has an impact on measurement of infrastructure development in Indonesia but, that's several research doesn't explore the correlation over the other regional growth's parameter [5,6,8,19,20]. This gap in empirical assessment is the focus of our research investigation.…”
mentioning
confidence: 97%
“…Indonesia, an archipelagic nation comprising thousands of islands, faces unique challenges in ensuring that infrastructure is both comprehensive and accessible across its vast geographical expanse. Over the past decades, the Indonesian government has embarked on ambitious infrastructure development initiatives to bridge regional disparities, stimulate economic growth, and enhance the quality of life for its citizens [19]. Infrastructure development also affects the availability of infrastructure that covers all regions of Indonesia and supports regional economic development.…”
mentioning
confidence: 99%